Clinical characteristics of Pneumocystis jirovecii pneumonia in hemodialysis patients - Na Young Kim; Na Young Kim; So Jeong Kim; So Jeong Kim; Yohwan Yeo; Taehee Kim; Taehee Kim; Ji-Young Park; Ji-Young Park; Jeong-Hee Choi; Jeong-Hee Choi; Chang Youl Lee; et al. (Frontiers in Medicine)
BackgroundLimited research exists on Pneumocystis jirovecii pneumonia (PJP) in hemodialysis (HD) patients. This retrospective study aimed to compare clinical features and outcomes of PJP in HD and non-HD patients.MethodsWe retrospectively analyzed 10 HD PJP cases and 40 non-HD PJP cases which were matched propensity scoring. Criteria included respiratory symptoms, new pulmonary infiltrates, and positive Pneumocystis real-time PCR. HD PJP patients were excluded if they were taking immunosuppressants, receiving solid organ transplant, treatment for hematological or solid cancer, HIV infection, or Pneumocystis jirovecii colonization, which was not an actual infection.ResultsNo significant differences in symptoms and radiological findings were observed between HD and non-HD PJP cases. Fever was the main symptom in both groups, ground glass opacity was the main finding on CT, and there was no significant difference between the two groups in blood test results. Although the partial pressure of oxygen/fraction of inspired oxygen (PaO2/FiO2) ratio and SpO2/FiO2 ratio exhibited lower averages in the HD group, there was no significant difference between the two groups (p = 0.562 and 0.693, respectively). HD PJP patients exhibited delayed time to treatment marginally (5.3 ± 2.3 days vs. 3.0 ± 3.8 days, p = 0.051) and duration of treatment was longer than non-HD PJP (18.3 ± 3.2 days vs. 13.5 ± 7.5 days, p = 0.015). The length of stay, in-hospital mortality, and PJP-related death rate did not differ between HD PJP and non-HD PJP (p = 0.382, 0.724, and 1.000, respectively).ConclusionOur study highlights that HD patients with PJP may encounter delays in diagnosis and treatment compared to non-HD PJP patients.